2019
DOI: 10.3889/oamjms.2019.231
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Soft Tissue Erdheim Chester Disease: Diagnostic Dilemma and Management

Abstract: BACKGROUND: Erdheim Chester disease (ECD) is a rare form of non-Langerhans histiocytosis that still presents a diagnostic and clinical dilemma. CASE PRESENTATION: We present a rare case of ECD, young 31 male with atypical localisation and soft tissue presentation and no bone involvement. He started clinical investigations due to subcutaneous tumour mass in the lumbar spine that caused severe back pain. Skin biopsy revealed ECD with Immunohistochemistry CD68+, CD10+, CD11c+, vimentin+, S100A4+. Activating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Ozkaya et al 12 also reported 2 patients presenting with subcutaneous soft tissue masses in the chest wall and upper back. An additional case presenting multiple nodular subcutaneous tumors in the back of a 31-year-old man was also reported; the tumor mass, in that case, seemed to be in continuity with the retroperitoneum 13 …”
Section: Authors Commentsmentioning
confidence: 91%
See 1 more Smart Citation
“…Ozkaya et al 12 also reported 2 patients presenting with subcutaneous soft tissue masses in the chest wall and upper back. An additional case presenting multiple nodular subcutaneous tumors in the back of a 31-year-old man was also reported; the tumor mass, in that case, seemed to be in continuity with the retroperitoneum 13 …”
Section: Authors Commentsmentioning
confidence: 91%
“…An additional case presenting multiple nodular subcutaneous tumors in the back of a 31-year-old man was also reported; the tumor mass, in that case, seemed to be in continuity with the retroperitoneum. 13 The diagnosis of ECD in cutaneous subcutaneous locations can pose a considerable challenge for pathologists. Cutaneous involvement shows nonspecific histologic features that can be easily confused for a variety of other benign histiocytic processes.…”
Section: Authors Commentsmentioning
confidence: 99%